The Prevalence of Tibiofemoral Knee Osteoarthritis Following Arthroscopic Partial Meniscectomy Is Variably Reported in General, and Over Time: A Systematic Review With a Minimum of 5-Year Follow-Up - Michael F. Masaracchio, P.T., Ph.D; Kaitlin Kirker, P.T., D.P.T; Parisa Loghmani, P.T., D.P.T; Jillian Gramling, S.P.T; Michael Mattia, P.T., D.P.T; Rebecca States, Ph.D., M.A (Elsevier, 2022)
Purpose: To assess the prevalence of tibiofemoral (TF) osteoarthritis (OA) following arthroscopic partial meniscectomy (APM) with a minimum follow-up of 5 years, to explore the prevalence of symptomatic TF OA, and to identify potential risk factors for the development of TF OA following APM. Methods: An electronic search was conducted using PubMed, CINAHL, Pedro, AMED, Embase, the Cochrane Library, and clinicaltrials.gov. Prospective/retrospective studies including participants with a mean age ≥18 years old, undergoing isolated APM, reported radiographic assessment of knee OA as an outcome, had at least 5-year follow-up, and were written in English were included. Two authors extracted relevant data. Four authors assessed methodologic quality using the Center of Reviews and Dissemination and the Downs and Black checklist. The prevalence of TF OA after APM was reported for each study, with the range provided across studies for each time period (5 years to <10 years, 10 years to <15 years, ≥15 years). Results: Twenty-two studies were included. Radiologic TF OA prevalence following APM ranged from 35% to 90%, 23% to 100%, and 52% to 57.7% at an average follow-up of 5 years to <10 years, 10 years to <15 years, and ≥15 years, respectively. Prevalence of symptomatic TF OA ranged from 24.1% to 67% according to individual operational definitions, with 2 studies reporting correlations between function and radiological findings. Conclusions: APM results in a prevalence of radiographic TF OA ranging from 23% to 100% across follow-up periods of 5 or more years with the lowest prevalence reported between 5 and <10 years and the highest prevalence reported between 10 and <15 years follow-up. Considerably less data was available to assess symptomatic TF OA or risk factors associated with TF OA. Level of Evidence: Level III, systematic review of Level II and III studies.